2022
DOI: 10.3390/foods11162428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Hulless Barley Flour on the Quality of Short-Dough Cookies

Abstract: Short-dough cookies are one of the most popular cereal-based products in the world, but usually they are considered as foods with a low nutritional value. Therefore, the aim of this study was to investigate the possibility of replacing part of the wheat flour (WF) with hulless barley flour (HLBF), in order to improve the functional properties and nutritional value of the cookies. Cookies were prepared from composite flours in the ratios HLBF:WF 0:100, 25:75, 50:50, 75:25, and 100:0. The results show that as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
(64 reference statements)
4
10
0
Order By: Relevance
“…The results revealed that the addition of barley flour (at 30% level) significantly increased their phenolic contents from 63 to 135 μg GAE/g for biscuits and from 237 to 287 μg GAE/g for chapattis. Related observations were found by Nakov et al (2022) for cookies supplemented with hull-less barley flour (at 25 -100% levels) as a partial substitute of wheat flour. They observed that the barley-enriched cookies had significantly higher total phenolics content (270.51 -621.42 µg GAE/g) and antioxidant capacity (2.15 -2.34 mmol Trolox equivalent (TE)/100g) than 100% WF cookies (160.53 µg GAE/g and 2.09 mmol TE/100g, respectively).…”
Section: Phytochemicals Composition Of Control and Supplemented Biscuitssupporting
confidence: 63%
See 2 more Smart Citations
“…The results revealed that the addition of barley flour (at 30% level) significantly increased their phenolic contents from 63 to 135 μg GAE/g for biscuits and from 237 to 287 μg GAE/g for chapattis. Related observations were found by Nakov et al (2022) for cookies supplemented with hull-less barley flour (at 25 -100% levels) as a partial substitute of wheat flour. They observed that the barley-enriched cookies had significantly higher total phenolics content (270.51 -621.42 µg GAE/g) and antioxidant capacity (2.15 -2.34 mmol Trolox equivalent (TE)/100g) than 100% WF cookies (160.53 µg GAE/g and 2.09 mmol TE/100g, respectively).…”
Section: Phytochemicals Composition Of Control and Supplemented Biscuitssupporting
confidence: 63%
“…In view of these results, there were not many changes in the color characteristics as a result of the partial replacement of wheat flour with barley flour (from hull-less and hulled barley varieties) up to 30% level and all supplemented biscuits revealed optimum color values. Related observations were found by Nakov et al (2022) for cookies supplemented with hull-less barley flour (at 25 -100% levels) as a partial substitute of wheat flour. They observed that the supplementation with barley flour did not affect the color characteristics of barley-enriched cookies significantly, especially at low and moderate incorporation levels.…”
Section: Color Characteristics Of Control and Supplemented Biscuitssupporting
confidence: 63%
See 1 more Smart Citation
“…Achieving the recommended value of the dynamic viscosity coefficient for a sample without stabilizing substances is impossible, which is due to the low content of dry substances, in particular fat. The use of Cremodan ® SI 320 and β-glucan in both cases increases the viscosity, but the highest value was observed for the ice cream mix with oat β-glucan, which can be explained by its high degree of free moisture adsorption and corresponding structuring [ 22 , 27 , 28 ]. The acidity of ice cream with Cremodan ® SI 320 and β-glucan decreases slightly, but falls within the generally known limits [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Burkus and Temelli [ 21 ] explained the positive effect of β-glucan on the overrun of ice cream by its synergistic interaction with milk proteins, which leads to the activation of surface-active properties of the “polysaccharide-protein” complex. However, an excessive amount of β-glucan can significantly deteriorate the texture of ice cream and negatively affect other physicochemical parameters [ 22 ], which must be taken into account when using this polysaccharide.…”
Section: Introductionmentioning
confidence: 99%